Design of distributed event-triggered circumnavigation control of a moving target by a group of underactuated surface vessels. (September 2022) - Ghommam, Jawhar; Rahman, Mohammad H.; Saad, Maarouf
Abstract: This paper investigates the localization and circumnavigation problem for a group of underactuated surface vessels (USVs). In particular, the USVs collaboratively locate an unknown moving target and then circumnavigate it isometrically with desired spacing angle and velocity. In this strategy, the target information is assumed to be known to only some vehicles in the group. First, a solution to the localization problem, is addressed from the perspective of event triggered distributed estimator (ETDE) to save limited communication resources. In terms of the Lyapunov functional method, it is shown through a novel sufficient criterion that the proposed distributed protocol guarantees the achievement of the localization while ensuring the exclusion of the Zeno-behavior. Second, due to the underactuation, actuators saturation and the uncertainties in the USVs model dynamics, existing distributed algorithms cannot be extended directly to achieve the circumnavigation objective. Under a dynamic event triggering strategy, a fully distributed exponential adaptive backstepping based control scheme is derived to ensure that the USVs move around the estimated target isometrically with a prescribed radius, circular velocity and inter-robot angular spacing. Moreover, to ensure prescribed transient behavior for line-of-sight range and heading tracking errors, an improved barrier function with time-varying scaling transformation is employed and incorporated within the control scheme. We show that under the event triggered communication, the proposed distributed control method, in the presence of uncertainties and actuator saturation, the circumnavigation problem is achieved with the tracking errors converging exponentially to a neighborhood of zero, while the constraint requirements on the line of sight (LOS) range and heading angle will never be violated.